Remote Education During the CODIV - 19 Pandemic – How to Motivate Yourself to Learn and Stay Motivated - Katarzyna SZMYD (Communications of International Proceedings, 2020)
The article attempts to approximate the topic related to the use of e - learning as a form of education and related opportunities to motivate participants to learn. Modern education must meet the demands of today's world. The CODIV-19 pandemic became the perpetrator that made remote learning no longer an experiment zone but a fact. This situation also allowed us to look at the nature of man and his motivation to learn in conditions other than traditional teaching. At the outset, the motivation that stimulates the body to act is characterized and the desire to achieve the goal. In turn, remote teaching is described as a support in the didactic process, taking into account its advantages and disadvantages. The study focuses on the role of lecturers - teachers as external motivators that stimulate and trigger the motivation of students - pupils to learn and thus to achieve their goals. As a summary of the considerations, the author presented examples of recommendations for lecturers conducting remote education.
Keywords: Motivation; E-Learning; Teacher; Process